What People Believe about Monetary Finance and What We Can('t) Do about It: Evidence from a Large-Scale, Multi-Country Survey Experiment - Cars Hommes; Julien Pinter; Isabelle Salle (Center for Economic Studies and ifo Institute (CESifo), 2023)
We conduct an information-provision experiment within a large-scale household survey on public finance in France, The Netherlands and Italy. We elicit prior opinions via open-ended questions and introduce a measure of macroeconomic policy literacy. A central bank (CB) educational blogpost explaining the mechanics of CB money preceded by a short video clip on public finance can persistently induce less support for monetary-financed proposals and more for fiscal discipline and CB independence, no matter the respondents' level of policy literacy. However, prior beliefs matter and contradictory information may be polarizing. Additional analysis of our data shows that information affects the respondents' views by shifting their inflation and tax expectations associated to these policies.
Keywords: E70; E60; E62; E58; G53; H31; C83; 330; large-scale household survey; information-provision experiment; RCT; central bank communication; expectations